2001
DOI: 10.1152/ajpgi.2001.281.4.g1101
|View full text |Cite
|
Sign up to set email alerts
|

nNOS in canine lower esophageal sphincter: colocalized with Cav-1 and Ca2+-handling proteins?

Abstract: Immunochemical studies with light microscopy, confocal microscopy, and electron microscopy were used to examine proteins associated with caveolin (Cav) in canine lower esophageal sphincter. The main Cav was Cav-1. It appeared to be colocalized at the cell periphery, in punctate sites, with immunoreactivity to antibodies against different COOH- and NH2-terminal epitopes of neuronal nitric oxide (NO) synthase (nNOS). One COOH-terminal-directed antibody, made in guinea pig, was used to colocalize other immunoreac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 50 publications
2
42
0
Order By: Relevance
“…Cav-3 is also expressed in gastrointestinal smooth muscle although its expression is less abundant than Cav-1. The role of Cav-3 is unknown relative to Cav-1 and PDE5 (7,10,30,47). It is possible that Cav-3 can subserve some of the roles of Cav-1 at a reduced level in the absence of Cav-1.…”
Section: Resultsmentioning
confidence: 99%
“…Cav-3 is also expressed in gastrointestinal smooth muscle although its expression is less abundant than Cav-1. The role of Cav-3 is unknown relative to Cav-1 and PDE5 (7,10,30,47). It is possible that Cav-3 can subserve some of the roles of Cav-1 at a reduced level in the absence of Cav-1.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanism of hSlo1 and Caveolin-1 Association-Positive evidence for a functional correlation or association between Slo1 and caveolin-1 has been observed in other tissues (5,(13)(14)(15)26). Pull-down experiments using glutathione S-transferase-caveolin-1 protein, and lysates of HEK293T cells expressing hSlo1 indicate that these two proteins can associate; however, an indirect binding cannot be ruled out (14).…”
Section: Association Of Slo1 Protein With Caveolin-1 In Native Aorticmentioning
confidence: 99%
“…Ϫ/Ϫ mice with anti-cav3 antibody and the antibody for nNOS-C, which recognizes the myogenic variant of nNOS (12), showed that cav3 immunoreactivity was found in the periphery of smooth muscle cells in the outer CM layer in both control and Cav1 Ϫ/Ϫ tissue (Fig. 2, b and e).…”
Section: Immunohistochemical Studiesmentioning
confidence: 89%
“…Cav1, -2, and -3 are a family of integral membrane proteins (21)(22)(23)(24) that are the principal components of the caveolar membrane in vivo (8,39). In smooth muscle and interstitial cells of Cajal (ICC), the most important caveolin is cav1 (12,14). They form homo-and heterooligomers that insert in the inner leaflet of plasma membrane to form the characteristic flask-shaped caveolae (47).…”
mentioning
confidence: 99%